IMPLEMETASI PEMBELAJARAN BERBASIS PROYEK PADA BIDANG KEJURUA - Herminarto Sofyan (Jurnal Cakrawala Pendidikan, 2006)
Vocational education is oriented to the formation ofprofessional competency. Such competency has to be supported bynn1~':l't1"0 abilities, the acquisitionthese abilitiesne'ed comprehensive learning experiences. Project-a making learning experiencesmore interesting and meaningful to university students,or, thoseundergoing transitional training when entering a fieldofwork~The project-based learning model helps learners (1) to learnhefty and meaningful useof knowledge and skill built throughassignments and works, (2) to increase knowledge through curricularactivities and the executionofopen-ended planning or investigation,and (3) to build knowledge through real-world experiences andinter-personal cognitive negotiations conducted in an atmosphereofcollaborative work.Project-based learning enables learners to learn moreactively. The instructor, or, anyone in chargeof the instructionalprocess, stands encouragingly behind learners, who makes theinitiatives. The instructor facilitates learners' projects and evaluateseach project in termsof its meaningfulness in and application ontheir daily life. Outcomes during the project represent results thatcan be measured authentically by the instructor in the learningprocess. So, in project-based learning, though not giving trainingactiveiy and directly, the instructor still has a role, as learninghelper, facilitator, and partner who understands students' think